Laying Down Paths in Talking with a Dutch Canadian Organizational Communication Ethnographer: Interview with Boris H. J. M. Brummans by Marie-Claude Plourde - Brummans, Boris H. J. M.; Plourde, Marie-Claude (Communiquer, 2023)
This interview traces the unfolding trajectories of Boris Brummans, an organizational communication ethnographer, in conversation with Marie-Claude Plourde.